William M. Fine papers - Fine, William M.
Correspondence, manuscript drafts, and production materials relating to Fine's book, That Day With God (1965), a collection of sermons and eulogies from all parts of the world delivered on the Sunday following the death of President John F. Kennedy. Correspondents include Richard Cardinal Cushing, Norma Millay (Ellis), Rose Kennedy, and Adele Simpson.
Author and editor.
Collection material in English.
Keywords: Cushing, Richard, -- 1895-1970 -- Correspondence; Millay, Norma -- Correspondence; Kennedy, John F. -- 1917-1963 -- Death and burial; Kennedy, Rose Fitzgerald, -- 1890-1995 -- Correspondence; Simpson, Adele -- Correspondence; Sermons, American; Authors; Editors